Functional food in the primary prevention of cardiovascular diseases - Mikulec, Anna; Zborowski, Marek; Klimczak, Agnieszka (Journal of Education, Health and Sport, 2022)
Cardiovascular diseases, metabolic disorders and obesity are a serious threat to civilization, especially in highly developed countries. Due to the number of deaths and complications they are among the health priorities in Poland. The aim of the study is to review the literature on the role of functional food in the primary prevention of cardiovascular diseases. Functional food, thanks to its antioxidant, hypocholesterolemic and anti-inflammatory properties, has a beneficial effect on lowering blood pressure, cholesterol levels, inhibiting LDL oxidation or inhibiting platelet aggregation. It is necessary to promote this type of food, because its action has a significant impact on the prevention of various diseases, especially cardiovascular, diet-related and civilization. Proper nutritional education is a way to improve human potential and health. Therefore, it is worth educating in order to promote these products and increase the interest in them as well as raise the nutritional awareness of the society.